Organizations as Constitutional Systems - Vanberg, Viktor (Sociologija. Mintis ir veiksmas, 1999)
Translation: Vanberg, Viktor. 1992. "Organizations as Constitutional Systems". Constitutional Political Economy. 3: 223-253. Translated by Zenonas Norkus. (First part of the article. The second one is published in the next issue of "Sociologija. Mintis ir veiksmas", 2000-1-2).